Use of offensive coefficient to analyse sport performance in indoor soccer - A. De Bortoli; R. De Bortoli; S. Márquez (Asociación Española de Ciencias del Deporte, 2010)
The objective was the study of the game action of indoor soccer teams through the analysis of offensive coefficients, verifying its relationship with field performance estimated by the final result of games. Competitions by the Federación Gaúcha de Fútbol Sala (Brasil) were followed for 9 years. Shots were divided into three different categories: 1) LAN: shots+finish line shots+goals; 2) MET: finish line shots+goals; and 3) GOL: goals. From those data the following indexes were obtained: 1) Offensive Outpout: (PO): ratio LAN of team 'A'/LAN of antagonist {PO = (LAN 'A'*100) / (LAN 'A'+LAN 'B')}; 2) Objectivity Index (IO): percentage of shots that reached the finish line {IO=(MET*100)/LAN}; 3) Proficiency Index (IA): percentage of shots transformed into goals {IA=(GOL*100)/LAN}; 4) Proficiency/Objectivity Rate (TA/O): percentage of shots reaching the finish line (MET) transformed into goals {TA/O=(GOL*100)/MET}; and 5) Game Volume (VJ): TA/O+PO+IO. Results obtained show that PO, IA and VJ were higher in winner than in loser teams. Ratio of PO corresponding to winners and losers was higher than those for IA or VJ. This study confirms the validity of the evaluation of performance through shot characterization and allows to conclude that IA is a better predictor of performance than PO; that is, the quality of shots is more important than its quantity.